2013
DOI: 10.1063/1.4850915
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations, heat evolution, and atomic diffusion during slow heating of Al-rich Al/Zr multilayered foils

Abstract: Articles you may be interested inEffect of Zr concentration on the microstructure of Al and the magnetoresistance properties of the magnetic tunnel junction with a Zr-alloyed Al-oxide barrier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…32 In particular, the latter indicated that the velocity bilayer curve for Ni-Al multilayer exhibits an anomalous velocity plateau, similar to what is observed experimentally with the Zr-Al system. 23 The study in Ref. 32 also suggested a thermal mechanism for the occurrence of this anomaly and observed that for the Ni/Al system the plateau occurs at bilayers such that w=d % 5%, where w is the premix width.…”
Section: Propagation Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…32 In particular, the latter indicated that the velocity bilayer curve for Ni-Al multilayer exhibits an anomalous velocity plateau, similar to what is observed experimentally with the Zr-Al system. 23 The study in Ref. 32 also suggested a thermal mechanism for the occurrence of this anomaly and observed that for the Ni/Al system the plateau occurs at bilayers such that w=d % 5%, where w is the premix width.…”
Section: Propagation Velocitymentioning
confidence: 99%
“…Consequently, the range of measured premixed widths can be quite wide. 23 We have not attempted a systematic analysis of the impact of w over the range of possible values, but have rather restricted our attention to two representative values, w ¼ 0.5 nm and w ¼ 0.8 nm. These values lie within a typical range of experimentally measured premixed widths and are sufficiently separated so as to lead to significant variations within the range of bilayers considered.…”
Section: Propagation Velocitymentioning
confidence: 99%
“…If the heat generated within an ignition zone is enough to initiate rapid mixing in the surrounding layers, then the reaction will self-propagate throughout the entire system. This idea has been applied to systems with different microstructures and chemistries [1][2][3], including core-shell particles [4][5][6][7][8], powder compacts [9][10][11][12][13][14], mechanically activated foils and powders [15][16][17][18][19], and vapor-deposited laminate foils [2,[20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Following recent experimental observations [38,39], the model assumes that the formation reaction is essentially complete prior to the start of the oxidation process. Thus, the initial foil temperature at the start of oxidation can be approximated as the adiabatic temperature corresponding to the anaerobic formation reaction.…”
Section: Model Formulationmentioning
confidence: 99%